2004
DOI: 10.1097/00126334-200412150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Couple Counseling Increases Uptake of Interventions to Prevent HIV-1 Transmission

Abstract: To determine effect of partner involvement and couple counseling on uptake of interventions to prevent HIV-1 transmission, women attending a Nairobi antenatal clinic were encouraged to return with partners for voluntary HIV-1 counseling and testing (VCT) and offered individual or couple posttest counseling. Nevirapine was provided to HIV-1-seropositive women and condoms distributed to all participants. Among 2104 women accepting testing, 308 (15%) had partners participate in VCT, of whom 116 (38%) were couple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
342
7
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(368 citation statements)
references
References 16 publications
16
342
7
3
Order By: Relevance
“…48,49 However, in spite of the available data and repeated recommendations, couple-centred approaches to HIV prevention (whether connected with PMTCT or prevention of sexual transmission) have not been implemented on a large scale or, at least, have not been documented in the literature, where others could learn from them. Apart from the experiences reported in Former Zaïre 37 , Rwanda, 38,57 , Zambia 3,14,43,44 , Kenya 45 , and the multi-site study KenyaTanzania-Trinidad 39,40 , it is hard to find in recent years any mention of a couple-centred approach in the scientific literature or in programmatic documents. * Even in the latest UNAIDS Global Report on HIV/AIDS, no mention is made of the potential of couple-centred approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 However, in spite of the available data and repeated recommendations, couple-centred approaches to HIV prevention (whether connected with PMTCT or prevention of sexual transmission) have not been implemented on a large scale or, at least, have not been documented in the literature, where others could learn from them. Apart from the experiences reported in Former Zaïre 37 , Rwanda, 38,57 , Zambia 3,14,43,44 , Kenya 45 , and the multi-site study KenyaTanzania-Trinidad 39,40 , it is hard to find in recent years any mention of a couple-centred approach in the scientific literature or in programmatic documents. * Even in the latest UNAIDS Global Report on HIV/AIDS, no mention is made of the potential of couple-centred approaches.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition to the couple VCT programmes described in the literature, two others were based in PMTCT programmes, one in Zambia and the other in Kenya (Table 2). 44,45 Both studies found very positive outcomes: couple counselling was associated with an increase in HIV testing acceptance, and in the uptake of antiretroviral prophylaxis and of formula feeding. In Zambia, there were no significant differences in reported adverse social events between couple-counselled versus individually-counselled women, but a trend towards a higher level of divorce or separation among serodiscordant couples was observed.…”
Section: Couple-centred Approaches To Hiv Counselling and Testingmentioning
confidence: 99%
“…Our study contributes to the body of literature that shows that men's support influences women's decisions to accept ART and PMTCT interventions. [32][33][34][35][36][37][38] Disclosure of HIV status has been associated with the acceptance of ART for PMTCT in studies in South Africa and Zimbabwe. [26,33,39] In univariate analysis, the odds of ART initiation among women who had disclosed their HIV status to their respective partners were higher than those of women who had not disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Number of studies on reproductive health in developing countries has suggested that involving men in reproductive health improves health outcomes. [9][10][11][12] It is important to determine husbands' knowledge and beliefs about cervical cancer and Pap smear screening test so that targeted interventions can be developed to increase their knowledge about cervical cancer and increase spousal support for cervical cancer screening. In this regard, the current paper tries to investigate the knowledge attitude, practice and health seeking behaviour about sexually transmitted infections (STIs) and cervical cancer among husbands in a slum community in Mumbai.…”
Section: Introductionmentioning
confidence: 99%